2016
DOI: 10.1097/shk.0000000000000650
|View full text |Cite
|
Sign up to set email alerts
|

Tlr2 on Bone Marrow and Non-Bone Marrow Derived Cells Regulates Inflammation and Organ Injury in Cooperation with Tlr4 During Resuscitated Hemorrhagic Shock

Abstract: Background Although the role of TLR4 in driving inflammation and organ injury after hemorrhagic shock and resuscitation (H/R) is well established, the role of TLR2 - another receptor for damage-associated molecular pattern (DAMP) molecules - is not. In this study, we used a combination of TLR2−/− and wild type (WT) mice treated with anti-TLR2 and anti-TLR4 neutralizing monoclonal antibodies (mAb) to discern the contribution of TLR2 relative to TLR4 to the systemic inflammatory response in murine H/R. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Cryostat sections of the tissues (6 µm) were stained with hematoxylin and eosin (H&E) to evaluate histopathologic cumulative changes among treatment groups. Images of five randomly selected fields were acquired using an Olympus Provis light microscope (Malvern, NY, USA) with 200× magnification ( 37 ).…”
Section: Methodsmentioning
confidence: 99%
“…Cryostat sections of the tissues (6 µm) were stained with hematoxylin and eosin (H&E) to evaluate histopathologic cumulative changes among treatment groups. Images of five randomly selected fields were acquired using an Olympus Provis light microscope (Malvern, NY, USA) with 200× magnification ( 37 ).…”
Section: Methodsmentioning
confidence: 99%
“…A recent finding has shown that anti-IL-5 antibody, IL-33, or ILC2 deletion, significantly increased IL-5 expression in neutrophils and decreased lung injury scores at 6 h in the HS-induced mice injury model ( 77 ). DAMPs can activate systemic inflammation and organ injury in HS through binding to TLR2 on immune cells ( 78 ). Similarly, anti-TLR2 monoclonal antibody or TLR2 -/- mice exhibited significantly less liver damage, and lower NF-κB and inflammatory cell infiltrate in HS at 20 h ( 78 ).…”
Section: New Insights Into Hs Therapeutics With Innate Immune Regulationmentioning
confidence: 99%
“…HS-associated lung injury is generally thought to develop in part due to reperfusion, which can cause cellular stress and the release of damage-associated molecular pattern (DAMP) molecules and inflammatory mediators, leading to leukocyte and vascular endothelial cell (EC) activation, increased capillary permeability, neutrophil infiltration, and tissue injury [12-15]. Cold-inducible RNA-binding protein (CIRP) is a highly conserved nuclear protein upregulated by hypoxia and mild hypothermia [16, 17].…”
Section: Introductionmentioning
confidence: 99%